Constructing S-scheme heterojunction of CoAlLa-LDH/g-C3N4 through monolayer Ti3C2-MXene to promote photocatalytic CO2 re-forming of methane to solar fuels - Azmat Ali Khan, Azmat Ali Khan (American Chemical Society, 2022)
Multi-heterostructure interfaces of CoAlLa-LDH with porous g-C3N4 on monolayer Ti3C2-MXene was designed to get double-S-scheme heterojunction through in situ grown titania nanoparticles using a single-step ultrasonic assisted hydrothermal approach. The Ti3C2 MXene nanotexture embedded TiO2 NPs provides 3D nanotexture for promoting the interface interaction of g-C3N4 with CoAlLa-LDH. The g-C3N4/Ti3C2T/CoAlLa-LDH dual-S-scheme assembly possesses merits of conductive and semiconductive components with higher charges separation. The photoactivity test was conducted for CO2 reduction through different re-forming systems such as dry re-forming of methane (DRM) and bi-re-forming of methane (BRM), whereas acidic and basic sites over the composite enabled the attachment of both the CO2 and CH4 molecules for their activation under solar energy. The electron rich composite resulted in CO and H2 production of 55.25 and 54.72 µmol g-1 h-1, respectively under visible light during DRM process. These amounts of CO and H2 were many folds higher than the pristine g-C3N4 and LDH samples. This significant performance was ascribed to the strong interfacial interaction with a dual-step-scheme formation and electron rich linkers of oxygen defective La/Ti sites for superior charge-transfer separation. More importantly, by introducing water to CO2/CH4, a further efficiency was enhanced due to more utilization of holes. The hydrogen rich syngas production through feed ratio and reducing agents with tremendous stability further endorses good sorption characteristics of newly developed nanotextures. This electrostatic attraction approach presented a promising route for the rational design of layered multicomponent heterojunctions with 2D/2D/2D architecture for CO2 reduction to solar fuels.